Clinical picture, outcome and predictive factors of lymphoma in primary Sjögren's syndrome: results from a harmonized dataset (1981–2021). (23rd December 2021) - Chatzis, Loukas G; Stergiou, Ioanna E; Goules, Andreas V; Pezoulas, Vasilis; Tsourouflis, Gerasimos; Fotiadis, Dimitrios; Tzioufas, Athanasios G; Voulgarelis, Michael
Abstract: Objectives: Primary Sjögren's Syndrome (pSS) carries the highest risk for non-Hodgkin's lymphoma (NHL) development among systemic autoimmune diseases. However, the paucity of data on the long-term survival of those patients and the lack of established predictors for each lymphoma histologic subtype prompted our present study. Methods: We retrospectively analysed 121 patients diagnosed with NHL according to the WHO classification criteria. All patients fulfilled the 2016 ACR-EULAR classification criteria for pSS. Cumulative clinical, laboratory, radiologic, treatment regimens and histologic data were recorded, harmonized and analysed. Overall survival (OS) and event-free survival (EFS) curves were calculated. A mucosa-associated lymphoid tissue lymphoma (MALTL) prediction model was developed by applying innovative data-driven analysis of clinical features present at the time of pSS diagnosis. Results: MALTLs constituted the majority of lymphomas (92/121, 76.0%) followed by diffuse large B-cell lymphomas (DLBCL) (11/121, 9.0%) and nodal marginal zone lymphomas (NMZL) (8/121, 7%). MALTLs show salivary glands localization, limited disease and often bone marrow and nodal involvement. The 10-year OS and EFS rates were 79% and 45.5% for MALTLs, 40.9% and 24.2% for DLBCL and 46% and 31% for NMZL. Cryoglobulinemia, focus score and the total EULAR SS Disease Activity Index (ESSDAI) composite index at pSS diagnosis were proven independent MALTL predictors. Even though MALTLs have a comparatively good survival outlook, they are accompanied by frequent events throughout their clinical course. Conclusions: Common features of pSS, present at diagnosis, can predict future lymphomagenesis meriting a more intensive follow-up plan.